Proton-Conductive Membranes Based on Blends of Polyimides - Okazaki, Y.; Nagaoka, S.; Kawakami, H.
We prepared novel proton-conductivity membranes based on blends of sulfonated polyimides. The blend membranes were prepared from a sulfonated homopolyimide and a sulfonated copolyimide with a solvent-casting method. The proton conductivities of the blend membranes were measured as functions of the temperature with four-point-probe electrochemical impedance spectroscopy. The conductivity of the membranes strongly depended on the sulfonated homopolyimide content and increased with an increase in the content. The proton conductivity of all the blended membranes indicated a higher value than that determined in Nafion at 80 8C, and this may mean that the proton transfer in the blend membranes is responsible for the ionic channels induced by the hydrophobic and hydrophilic domains.
Keywords: BLENDS; FUEL CELLS; MEMBRANES; POLYIMIDES; PROTON CONDUCTIVITY; SULFONATED POLYIMIDES; WATER UPTAKE